2019
DOI: 10.5194/bg-16-4183-2019
|View full text |Cite
|
Sign up to set email alerts
|

Organic-carbon-rich sediments: benthic foraminifera as bio-indicators of depositional environments

Abstract: Abstract. Fjords have been described as hotspots for carbon burial, potentially playing a key role within the carbon cycle as climate regulators over multiple timescales. Nevertheless, little is known about the long-term fate of the carbon that may become stored in fjordic sediments. One of the main reasons for this knowledge gap is that carbon arriving on the seafloor is prone to post-depositional degradation, posing a great challenge when trying to discriminate between an actual change in the carbon depositi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…The low foraminiferal abundance at the highest oxygen concentration is attributed to the difference in organic matter and predatory pressure (Figure 4(B)). Increased benthic foraminiferal abundance in a region is often attributed to the high organic carbon content of the sediments (Cappelli et al, 2019; Chaturvedi et al, 2000; Singh et al, 2021). The prevalence of macrobenthic communities also adversely affects benthic foraminifera by inducing high predatory pressure (Enge et al, 2016; Levin, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The low foraminiferal abundance at the highest oxygen concentration is attributed to the difference in organic matter and predatory pressure (Figure 4(B)). Increased benthic foraminiferal abundance in a region is often attributed to the high organic carbon content of the sediments (Cappelli et al, 2019; Chaturvedi et al, 2000; Singh et al, 2021). The prevalence of macrobenthic communities also adversely affects benthic foraminifera by inducing high predatory pressure (Enge et al, 2016; Levin, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Sediment is a key component that controls ecological functions, food production and many other processes at the Earth's surface. Benthic foraminifera are sensitive to changes in sediment texture (Zallesa et al 2014, Abuzied et al 2016) and organic carbon content (Cappelli et al 2019). Foraminiferal densities increased towards the deeper continental shelf zones, correlated with an increase in fine-grained sediment and total organic matter, according to Martins (2019), whereas low density of foraminifera is found in shallow stations due to sediment instability and lack of food quality associated with organic matter.…”
Section: Physicochemical Parametersmentioning
confidence: 99%
“…Current energy and water depth influence grain size distribution and sediment sorting (Lidz et al 1965). Cappelli (2019) found that the small size fraction (63-150mm) has the most diagnostic species and the greatest species diversity and richness, providing a more robust statistical foundation for high-resolution environmental reconstructions. Under oxygenated conditions, a group of foraminifera including Caronia silvestrii, Epistominella vitrea and Acostata mariae were strongly affected by labile organic matter in samples collected from the Po river outlet, northern Adriatic Sea, demonstrating habitat distribution by migration towards the sediment-water interface (Ernst et al 2005).…”
Section: Physicochemical Parametersmentioning
confidence: 99%
“…Initial examination of these characteristics indicated that smaller fjards were not comparable to the larger fjords. The disparity between these types of systems has previously been observed in Scotland, where the fjards of the Shetland Islands were categorized as distinct systems separate from the fjords of the mainland and Hebridian Islands (Lo Giudice Cappelli et al, 2019;, therefore for the purposes of the study the six fjards (Figure 4) were excluded from the data mining exercise.…”
Section: A National Inventory Of Oc Terr In Scotland's Mid-latitude F...mentioning
confidence: 99%